Analysis of Factors Affecting the Decision to Grant “KUR” in the Agricultural Sector at PT XYZ in Malang District, Indonesia - Jihad, Fajri Dhaniar Mohammad; Riana, Fitria Dina (Agro Bali : Agricultural Journal, 2025)
Small enterprises frequently struggle with funding, which is why the government has responded by distributing People's Business Credit (KUR) as a solution. This kind of loan is a soft credit meant for small business owners with feasible ventures but little funding. This study aims to determine the influence of several factors on the decision to grant People's Business Credit (KUR) in the agricultural sector by PT XYZ in Malang District, Indonesia, focusing on the history of relationships with banks, business experience, business profits, and the amount of the proposed loan. This study uses a quantitative approach with data collected through questionnaires. The population consists of business owners in the agricultural sector who utilize government-provided KUR funds. The sampling technique used is cluster sampling at Bank XYZ. The sample in this study consists of 307 agricultural entrepreneurs who benefit from the KUR funds provided by Bank XYZ. The results of this research show that: Factors that influence the decision of Bank XYZ Singosari Unit in granting People's Business Credit (KUR) in the agricultural sector include the history of relationships with banks, business experience, business profits, and the amount of the proposed loan has a significant effect on the decision to grant KUR. While the term of the proposed loan does not affect the decision to grant KUR, the dominant factor that most influenced the decision to grant KUR to prospective debtors in the agricultural sector, based on the value of the effective contribution, was the business experience variable.